Design and Development of an Online Catering Ordering Information System Using the Prototype Methodology - Fadaniel Herzah, Haby; Peratama Islam, Rizky; Shifa Fauziah, Revi; Kanaya Marlan, Azizah; Indri Wulan Ningsih, Citra (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2024)
This study develops a web-based online catering ordering system to address issues in traditional catering, such as manual order errors, delayed information delivery, and data inconsistencies. Using the Prototype methodology, the system was iteratively designed with user feedback to ensure functionality and usability. The primary goals are to enhance operational efficiency, improve service accuracy, and deliver a seamless digital experience. Key features include user registration, secure login, interactive menu selection (à la carte or buffet), dynamic order forms for specifying portions and delivery dates, and admin tools for order management and automated sales reporting. The interface is responsive, accessible across devices, with non-functional requirements ensuring data encryption, 24/7 availability, and sub-2-second response times. The development followed the Prototype lifecycle: requirements gathering, system design (using ERD, Use Case, Class, Activity, and Sequence Diagrams), web-based implementation, black-box testing, and ongoing maintenance for bug fixes and performance optimization. Testing validated reliable login, ordering, and payment processes, handling edge cases effectively. This system streamlines catering operations, reduces errors, and enhances customer satisfaction, offering a scalable solution for food services. Future enhancements may include mobile app integration and advanced analytics.